PENGARUH PENYAKIT GINJAL KRONIK TERHADAP DISFUNGSI EREKSI PRIA - Simanjuntak, Boni N. (e-Biomedik, 2014)
Abstract: Chronic kidney disease is decreased in kidney function that persistent and irreversible. Chronic kidney disease can lead to problems in the erectile function of men because of disorders on some factors, that are the endocrine system, the vascular system, psychological factor, and neurogenic disorder. WHO estimated that there will be an increasing number of patients with chronic kidney disease by 41.4% between the years 1995-2025 in Indonesia. Research on erectile dysfunction in patients with chronic kidney disease has not been done yet in Indonesia, especially in Manado. The Aim of this research is to know the effect of chronic kidney disease to erectile dysfunction of men. The research design for this study is observasional descriptive. The number of samples obtained as many as 34 samples of patients with stage 5 chronic kidney disease, be found 18 people (52.95%) suffering from mild erectile dysfunction, 12 people (35.29%) suffering from mild-moderate erectile dysfunction, a man (2.94%) suffering from moderate erectile dysfunction, 2 people (5.88%) suffering from severe erectile dysfunction, and a man (2.94%) with no erectile dysfunction. The conclusion is patients with chronic kidney disease can lead to problems in the erectile function, because of influence from the above factors. Suggestion on this research is necessary to check blood testosterone levels and find more samples. Key word : Chronic kidney disease, erectile dysfunctionÂ Â  Abstrak: Penyakit ginjal kronik adalah penurunan fungsi ginjal yang bersifat persisten dan ireversibel. Penyakit ginjal kronik dapat mengakibatkan masalah pada fungsi ereksi pria karena gangguan pada beberapa faktor, yaitu sistem endokrin, sistem vaskuler, faktor psikologis, dan kelainan neurogenik. WHO memperkirakan di Indonesia akan terjadi peningkatan jumlah penderita penyakit ginjal kronik sebesar 41,4% diantara tahun 1995-2025. Penelitian tentang disfungsi ereksi pada penderita penyakit ginjal kronik belum banyak dilakukan di Indonesia terutama di Manado. Penelitian ini bertujuan untuk mengetahui pengaruh penyakit ginjal kronik terhadap disfungsi ereksi pria. Desain penelitian yang digunakan adalah observasional deskriptif. Jumlah sampel yang didapat sebanyak 34 sampel penderita ginjal kronik stadium 5, didapatkan 18 orang (52,95%) menderita disfungsi ereksi ringan, 12 orang (35,29%) menderita disfungsi ereksi sedang-ringan, 1 orang (2,94%) menderita disfungsi ereksi sedang, 2 orang (5,88%) menderita disfungsi ereksi berat, dan 1 orang (2,94%) tidak disfungsi ereksi. Kesimpulan yang diperoleh adalah dapat terjadi gangguan fungsi ereksi pada penderita penyakit ginjal kronik, karena dipengaruhi oleh faktor diatas. Saran pada penelitian ini adalah perlu dilakukan pemeriksaan kadar testosteron darah dan mencari sampel yang lebih banyak. Kata kunci : Penyakit ginjal kronik, disfungsi ereksi